A new species of broad-leafed Anthurium (Araceae) from the central region of Veracruz, Mexico - Jiménez, Pedro Díaz; Croat, Thomas B.; Amith, Jonathan D.; Pérez-Farrera, Miguel Ángel; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2024)
We describe and illustrate Anthurium tiswatl, a new species of Anthurium sect. Andiphilum from Veracruz, Mexico. It is morphologically similar to A. macdougallii, but differs from that species in having long cataphylls, blades and spadix, collective veins arising from the first or fifth pairs of basal veins, and yellowish to whitish berries when ripe.